2022
DOI: 10.3389/fneur.2022.1022292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the non-auditory neurocognitive test MoCA-HI for hearing-impaired

Abstract: BackgroundSince hearing loss and cognitive decline often co-occur among older adults, a cognitive screening test suitable for hearing-impaired people is of high clinical relevance. We report the first evaluation of a German language version of the Montreal Cognitive Assessment—Hearing Impaired version (MoCA-HI).ObjectiveThe aim of the present study was to compare cognitively healthy participants with and without hearing loss, to examine the impact of age, sex, educational level and degree of hearing impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Previous research has demonstrated that measures of cognition may be underestimated if sensory impairments are not considered or adjusted for ( 68 , 69 ). Efforts have been made to develop or adapt cognitive tests for people with hearing impairment ( 70 , 71 ). However, a scoping review of cognitive screening and assessment tools adapted for people with sensory impairment found that the sensitivity and validity of these instruments is poor ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that measures of cognition may be underestimated if sensory impairments are not considered or adjusted for ( 68 , 69 ). Efforts have been made to develop or adapt cognitive tests for people with hearing impairment ( 70 , 71 ). However, a scoping review of cognitive screening and assessment tools adapted for people with sensory impairment found that the sensitivity and validity of these instruments is poor ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 Another study revealed that compared to individuals with moderate to profound hearing loss, those with normal hearing or mild hearing loss performed similarly on the MoCA Hearing Impaired Version (MoCA-HI) 20 but significantly better on the standard MoCA. 21 Previous literature also revealed that studies frequently use subjective participant reporting rather than measured hearing thresholds to characterize hearing ability. 3 This is of concern because subjective reports of hearing have been found to underestimate hearing loss in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, results from a study examining performance on the Montreal Cognitive Assessment (MoCA), a cognitive screening, revealed that a greater proportion of individuals with normal hearing pass than those with hearing loss, a relationship that persists despite the removal of auditory test components 4 . Another study revealed that compared to individuals with moderate to profound hearing loss, those with normal hearing or mild hearing loss performed similarly on the MoCA Hearing Impaired Version (MoCA‐HI) 20 but significantly better on the standard MoCA 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it is an imperative to reliably detect cases of cognitive impairment. Due to the high comorbidity of hearing loss and cognitive impairment ( Lin et al, 2013 ; Teipel et al, 2015 ; Fritze et al, 2016 ; Huang et al, 2023 ; Tamblay et al, 2023 ), cognitive screening has gained increasing awareness beyond geriatric or psychiatric settings ( Mordenfeld et al, 2020 ; Susano et al, 2020 ; Canavan and O’Donnell, 2022 ; Jammula et al, 2022 ; Tsui et al, 2022 ) including ENT departments and audiology ( Mosnier et al, 2018 ; Humes, 2020 ; Sanders et al, 2021 ; Völter et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%